Self-Silencing and Rejection Sensitivity as Predictors of Depression in Adolescent Girls - Popescu, Andreea; Karna, Wioleta; Petrov, Georgi (Psychology of Woman Journal, 2024)
Objective: This study aimed to investigate the predictive roles of self-silencing and rejection sensitivity on depression in adolescent girls. Methods and Materials: A correlational descriptive design was employed with 440 adolescent girls recruited from high schools across Poland. Participants completed standardized self-report measures assessing depression, self-silencing, and rejection sensitivity. Data collection adhered to ethical guidelines, and informed consent was obtained from all participants and their guardians. Descriptive statistics were used to summarize the data, and assumptions of normality and linearity were verified before inferential analyses. Pearson’s correlation examined the relationships between variables, and a standard linear regression model was conducted using SPSS-27 to determine how self-silencing and rejection sensitivity predict depression. Findings: Both self-silencing and rejection sensitivity exhibited strong positive correlations with depression. The linear regression analysis showed that the model significantly accounted for 41% of the variance in depression scores. Rejection sensitivity emerged as the slightly stronger predictor, although both predictors contributed uniquely to depressive outcomes. All inferential tests were statistically significant with p < 0.01, highlighting the importance of these interpersonal and intrapersonal variables in understanding depressive symptoms among adolescent girls. Conclusion: The findings suggest that high levels of self-silencing and rejection sensitivity are potent risk factors for depression in adolescent girls. Interventions that foster healthy emotional expression and address fear of rejection may be particularly beneficial for reducing depressive symptoms. Early detection and targeted support can potentially mitigate the negative impact of these factors and promote better mental health during adolescence.